Analisis Pelaksanaan Komunikasi Informasi Edukasi (KIE) Kesehatan Reproduksi dan Seksual pada Calon Pengantin di Kota Bukittinggi Tahun 2019 - Darmayanti Darmayanti; Supiyah Supiyah; Rosa Mesalina (Poltekkes Kemenkes Padang, 2020)
The reproductive and Sexual health information Communication (KIE) program for bride couple is a program that is implemented to prepare for family life. However, the implementation of KIE reproductive and sexual health for bride couple has not been carried out wording the standards caused by various factors in both the input, process, output aspects. The purpose of this research is to know the implementation of the program KIE Reproductive health and sexual bride couple. This type of research is qualitative research with a phenomenological approach. Research conducted in Bukittinggi with 48 informants. Sampling technique with purposive sampling. The instrument used guided interview guidelines conducted with In-depth interview and focus group discussion covering aspects of input, process, the output of the program KIE Reproductive and sexual health. Data is analyzed by textual analysis and thematic analysis. The thematic analysis relates to the absence of local policies, limited use of media, availability and limited Human Resources qualification, unstandardized implementation mechanisms, coverage of bride couple that accept the unmeasured KIE services. Required a regulation governing the implementation of the reproductive and sexual health of the bride couple for more positive impact on both short and long-term maternal and child health.